â€œANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PREMIER AUTO DETAILING SEMARANGâ€. - Rahardjo, Ricky; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2016)
This study aims to examine and analyze the Influence of Service Quality Customer Satisfaction Premier Auto Detailing Semarang. The population that will be used in this study consists of customers Premier Auto Detail Semarang. In this research, sampling is done with a technique accidental. Thus meaning the sample was taken as a Premier Auto Detail Customers who happened to be found at the Office of the Premier Auto Detail, the number of samples used in this study were 100 respondents.The results showed that the physical evidence (tangibles) against direct impact on customer satisfaction, reliability (reliability) effect lansgung to customer satisfaction, responsiveness (responsiveness) directly affects customer satisfaction, assurance (assurance) directly affects customer satisfaction , empathy (empathy) directly affects customer satisfaction